2011
DOI: 10.4028/www.scientific.net/amr.347-353.2604
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Oil Production by Pyrolysis and Liquefaction of Biomass Using Blast Furnace Slag as Heating Source

Abstract: In this paper, a novel biomass pyrolysis and liquefaction system using blast furnace as heating source was presented. The system is composed of three parts: blast furnace slag granulation, biomass pyrolysis centrifuge reactor, and the waste heat of blast furnace as the heat source. As the cost of biomass pyrolysis was greatly reduced, this system has a promising application prospect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Zuo et al found that the addition of copper slag during low-temperature pyrolysis of different biomass increased the hydrogen content and reduced the CO content in gaseous products. Luo et al , reported that a maximum yield of bio-oil (57.3 wt %) was obtained by co-pyrolysis of pine sawdust and slag, with the particle size of 2 mm, at 650 °C. Duan et al employed an electric heating tube furnace to simulate the heating of coal by blast furnace slag, and the yield of char decreased with the increase of the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Zuo et al found that the addition of copper slag during low-temperature pyrolysis of different biomass increased the hydrogen content and reduced the CO content in gaseous products. Luo et al , reported that a maximum yield of bio-oil (57.3 wt %) was obtained by co-pyrolysis of pine sawdust and slag, with the particle size of 2 mm, at 650 °C. Duan et al employed an electric heating tube furnace to simulate the heating of coal by blast furnace slag, and the yield of char decreased with the increase of the temperature.…”
Section: Introductionmentioning
confidence: 99%